Development and Validation of the Pre-Service Teacher Online Teaching Motivation Scale (PST-OTMS) - Bennett, Luke; Smart, Julie; Wiles, Daphne; Morrison, Anna; Zhang, Zhuo; Bowman, Alexander; Maeda, Yukiko; Doane, Braiden (Online Learning, 2024)
The purpose of the current study was to develop and validate the Pre-Service Teacher Online Teaching Motivation Scale (PST-OTMS), a survey instrument designed to reliably measure motivational constructs related to online teaching and learning in pre-service teachers. Due to increasing opportunities to teach within online learning contexts where challenges were magnified during the COVID-19 pandemic, a reliable and valid instrument is needed to measure such motivational constructs. The Pre-Service Teacher Online Teaching Motivation Survey (PST-OTMS) underwent a thorough validation process resulting in a 31-item survey aimed at assessing pre-service teacher motivation for online teaching across four dimensions: (1) pre-service teacher self-efficacy for online teaching, (2) pre-service teacher perceptions of online teaching and learning, (3) online teaching professionalism, and (4) pre-service teacher anticipated administrative support for online teaching. The PST-OTMS demonstrated strong reliability and validity within the research context. Future research aims to widely administer the PST-OTMS to explore reliability and validity within additional settings and with a more diverse demographic.